PHARMACOGNOSTICAL AND PHYTOCHEMICAL EVALUATION OF TENDER AND MATURE LEAVES OF MANGIFERA INDICA LINN. - Salahudeen, *Surumi; Eapen, Jollykutty; Indulekha, V.C (International Journal of Ayurveda and Pharma Research, 2018)
Amrapallava, which is identified as tender leaves of mango tree (Mangifera indica Linn) are used for various ailments in Ayurvedic system of medicine since ancient time. But there is no scientific data is available on different maturity levels of leaves for therapeutic use. Hence the present study compared the Pharmacognostical and Phytochemical standards of the leaves of Mangifera indica Linn at different maturity. Macroscopic, microscopic, physicochemical, phytochemical, TLC, HPTLC and AAS tests were done as per the standard procedure described in Ayurveda Pharmacopoeia of India. Among the macroscopic characteristics, the colour of tender leaves of Mangifera indica Linn is pinkish, amber or pale green colour while that of mature leaves having dark green colour. Texture of tender and mature leaves of Mangifera indica Linn was thin leathery and coriacious respectively. In transverse section the resin canal was more in mature leaves of mango tree. Tetrahedral prismatic crystals are present in tender leaves which is absent in mature leaves. The percentage of water soluble extractive and fibre content was comparatively more in mature leaves. Steroids were absent in both tender and mature leaves. Percentage of Phenolic content was more in mature leaves, and there is no other marked variation in all other parameters.